Optimization of the Nano-Dust Analyzer (NDA) for operation under solar UV illumination. (15th December 2015) - O׳Brien, L.; Grün, E.; Sternovsky, Z.
Abstract: The performance of the Nano-Dust Analyzer (NDA) instrument is analyzed for close pointing to the Sun, finding the optimal field-of-view (FOV), arrangement of internal baffles and measurement requirements. The laboratory version of the NDA instrument was recently developed (O׳Brien et al., 2014 ) for the detection and elemental composition analysis of nano-dust particles. These particles are generated near the Sun by the collisional breakup of interplanetary dust particles (IDP), and delivered to Earth׳s orbit through interaction with the magnetic field of the expanding solar wind plasma. NDA is operating on the basis of impact ionization of the particle and collecting the generated ions in a time-of-flight fashion. The challenge in the measurement is that nano-dust particles arrive from a direction close to that of the Sun and thus the instrument is exposed to intense ultraviolet (UV) radiation. The performed optical ray-tracing analysis shows that it is possible to suppress the number of UV photons scattering into NDA׳s ion detector to levels that allow both high signal-to-noise ratio measurements, and long-term instrument operation. Analysis results show that by avoiding direct illumination of the target, the photon flux reaching the detector is reduced by a factor of about 10 3 . Furthermore, by avoiding the target and also implementing a low-reflective coating, as well as an optimized instrument geometry consisting of an internal baffle system and a conical detector housing, the photon flux can be reduced by a factor of 10 6, bringing it well below the operation requirement. The instrument׳s FOV is optimized for the detection of nano-dust particles, while excluding the Sun. With the Sun in the FOV, the instrument can operate with reduced sensitivity and for a limited duration. The NDA instrument is suitable for future space missions to provide the unambiguous detection of nano-dust particles, to understand the conditions in the inner heliosphere and its temporal variability, and to constrain the chemical differentiation and processing of IDPs. Highlights: The performance of NDA while pointed close to the Sun is analyzed. The UV noise limit that will allow NDA to make sensitive measurements is defined. NDA design is optimized to reduce photon scatter into detector to the required level. Limitations on NDA pointing geometry, FOV, and sensitive dust measurements are reported.